Intersubject local SAR variation for 7T prostate MR imaging with an eight-channel single-side adapted dipole antenna array - Ipek, Özlem; Raaijmakers, Alexander J.; Lagendijk, Jan J.; Luijten, Peter R.; van den Berg, Cornelis A. T. (Magnetic resonance in medicine, 2014)
Purpose Surface transmit arrays used in ultra‐high field body MRI require local specific absorption rate (SAR) assessment. As local SAR cannot be measured directly, local SAR is determined by simulations using dielectric patient models. In this study, the inter‐patient local SAR variation is investigated for 7T prostate imaging with the single‐side adapted dipole antenna array. Method Four‐dedicated dielectric models were created by segmenting Dixon water–fat separated images that were obtained from four subjects with a 1.5T scanner and the surface array in place. Electromagnetic simulations were performed to calculate the SAR distribution for each model. Radio frequency (RF) exposure variations were determined by analyzing the SAR10g distributions (1) with one element active, (2) using a Q‐matrix eigenvalue/eigenvector approach, (3) with the maximum potential SAR in each voxel, and (4) for a phase shimmed prostate measurement. Results Maximum potential local SAR levels for 1 W time‐averaged accepted power per transmit channel range from 4.1 to 7.1 W/kg. Conclusion These variations show that one model is not sufficient to determine safe scan settings. For the operation of the surface array conservative power settings were derived based on a worst‐case SAR evaluation and the most SAR‐sensitive body model. Magn Reson Med 71:1559–1567, 2014. © 2013 Wiley Periodicals, Inc.